Car Trajectory Correction and Presentation Using Google Maps - Pleva, Matus; Cizmar, Anton (Communications - Scientific Letters of the University of Zilina, 2015)
This paper describes a trajectory correction algorithm which calculates the kinetic parameters of the tracked object (car using GPS data from tracking device) and detects faulty GPS samples. Input parameters contain GPS geographical coordinates of the object and the timestamp code of capturing the position. Based on these data and physical object limits, which the operator could modify, the algorithm decides if the sample is precise or faulty. In the case of faulty sample the algorithm suggests the estimated location of the point using Kalman filter implementation and the results are presented on the map using online web interface. When the operator confirms a predicted sample, the previous predicted (not confirmed samples) are recomputed using a backward correction algorithm. The final corrected trajectory is presented using a developed specialized interactive web interface with embedded Google maps API.
Keywords: Kalman filter; route correction; GPS; trajectory; Google maps API